Pengaruh Transportasi Daring Terhadap Ketahanan Ekonomi Pengemudi (Studi di Wilayah Kota Yogyakarta DIY)i Di Wilayah Kota Yogyakarta) - Prasetya, Lukman Dwi (Jurnal Ketahanan Nasional, 2024)
This research studied factors causing people to become online transportation drivers and to analyze the impact of income and expenses on the economic resilience of drivers. This research uses a quantitative approach through questionnaires. The quantitative data analysis technique was done using multiple linear regression, along with data presentation and conclusion drawing. The results of the study indicate that, first, the factors motivating people to become online transportation drivers are more flexible working hours, economic demands, and better income. Second, the income received by online transportation drivers generally exceeds the minimum wage in Yogyakarta City, and the monthly expenses of the drivers exceed the poverty line in the DIY province, contributing to better economic resilience.